Pemupukan NPK Phonska dan Jenis Tumpang Sari Terhadap Pertumbuhan Tanaman Pisang Rutai (Musa borneensis Becc.) - Purwati Purwati; Abdul Rofik (Agrifarm : Jurnal Ilmu Pertanian, 2018)
Rutai banana plants are local plants from Kutai Kartanegara Regency. But the existence of this plant has begun to be rare in the farmer's garden. Rutai bananas are small and are very popular for many people because of their distinctive aroma and sweet taste with high vitamin content. The small fruit shape is very suitable to be an appetizer at restaurants or food stalls. The Kutai Kartanegara District Government has made Rutai banana as an obligatory appetizer in Kutai Kartanegara. From the results of research on rutai banana fertilization on farmers' land shows very high productivity so it is necessary to do research to determine the growth of rutai banana planted intercropping with food crops. This is because the rutai banana plant uses a spacing of 3 mx 3 m, so that between banana plants there is still room that can be used for cultivation of food crops. This study aims to examine the effectiveness of NPK Phonska fertilization and the type of intercropping in rutai banana cultivation. This study used a Randomized Block Design (RBD) consisting of 4 treatments with 5 replications. Intercropping treatment consists of 4 levels, namely: s0 = without intercropping, without fertilization, s1 = without intercropping and NPK Phonska fertilizer 0.5 kg / tree, s2 = intercropping of chili and Phonska NPK 0.5 kg / tree , s3 = intercropping of corn plants and 0.5 kg / tree Phonska NPK fertilizer. Data obtained from observations were analyzed by variance and further testing with BNT at the level of 5%. Research activities include (1) land preparation (2) planting rutai banana seeds and ginger seedlings (3) Phonska NPK fertilizer treatment (4) Bioculture fertilizer treatment (5) POC Nasa fertilizer treatment (6) maintenance (7) data collection. The results showed that NPK Phonska fertilization was 0.5 kg / tree and intercropping with corn plants showed the best growth of rutai banana.